Generalized Myasthenia Gravis Diagnosed After Blepharoplasty - Murat Alemdar; Mustafa Karabacak (Türk Nöroloji Dergisi, 2021)
Neuromuscular junction disorders should not be missed in the differential diagnosis of ptosis. A 69-year-old male patient was admitted to our clinic with droopy upper eyelids, prominent in the left side for 6 months. Attributing his eyelid skin sag to aging, blepharoplasty was performed 5 months ago. He was referred to our department after no benefit was observed from operation. He reported difficulty in walking and climbing stairs, and getting fatigued while chewing food. In repetitive nerve stimulation studies, a significant decremental response was observed in the compound muscle action potential amplitudes recorded from the nasalis muscle with repetitive stimulation of the facial nerve on both sides, and the trapezius muscle with the stimulation of the left accessory nerve. Computed tomography of the thorax was normal. His serum acetylcholine receptor antibody level was elevated (40.7 nmol/l). He was diagnosed as myasthenia gravis and pyridostigmine therapy was recommended. He described a definite improvement in his complaints ten days later on control visit. The history of this late-diagnosed patient presenting with ptosis emphasizes the importance of questioning additional findings like diplopia, chewing-swallowing difficulties, weakness in proximal muscles, and questioning whether there is an increase in those complaints due to fatigue.